Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Divisi Logistik CV. Sinar Laut Palembang - Mahdi Hendrich; Anton Trianto; Imam Suroso; Vivin Afini; Khairuddin (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2019)
This research is conducted at Logistics Division CV. Sinar Laut Palembang.This is a private company engaged in the distribution of food productions that has been established for approximately 40 years. This study aims to look at the effect of motivation and disciplineon employee performance in the company unit.By using purposive sampling method, the data used a reprimary data using the help of aquestionnaire instrument. The analytical tool used is multiple linear regressions processed by SPSS 25 software. Based on the data analysis, it can be concluded that Motivationvariable (X1)has a significant effecton employee performance(Y). t table is 3.524>1.994, Motivation Variables and Discipline Variables simultaneously affect Employee Performance Variables, shown by F value of 13.989> F table 3.13. It can be concluded that Motivation and Discipline affect employee performance at Logistics Division CV. SinarLaut.